Impacts of China's Accession to the World Trade Organization - Ianchovichina, Elena; Martin, Will (Washington, DC: World Bank, 2014)
This article presents estimates of the impact of China's accession to the World Trade Organization (WTO). China is estimated to be the biggest beneficiary (US$31 billion a year from trade reforms in preparation for accession and additional gains of $10 billion a year from reforms after accession), followed by its major trading partners that also undertake liberalization, including the economies in North America, Western Europe, and Taiwan (China). Accession will boost manufacturing sectors in China, especially textiles and apparel, which will benefit directly from the removal of export quotas. Developing economies competing with China in third markets may suffer small losses. Accession will have important distributional consequences for China, with the wages of skilled and unskilled nonfarm workers rising in real terms and relative to those of farm workers. Possible policy changes, including reductions in barriers to labor mobility and improvements in rural education, could more than offset these negative impacts and facilitate the development of China's economy.